Clinicopathological characteristics and outcome of 31 patients with ETV6-NTRK3 fusion gene confirmed (mammary analogue) secretory carcinoma of salivary glands. (July 2018) - Boon, E.; Valstar, M.H.; van der Graaf, W.T.A.; Bloemena, E.; Willems, S.M.; Meeuwis, C.A.; Slootweg, P.J.; Smit, L.A.; Merkx, M.A.W.; Takes, R.P.; Kaanders, J.H.A.M.; Groenen, P.J.T.A.; et al.
Highlights: We evaluated 31 patients with secretory carcinoma of salivary glands. Clinical outcomes were generally good with 5- and 10-year overall survival of 95%. One patient developed a local recurrence, no regional or distant recurrences. Elective neck treatment does not seem indicated given the excellent outcomes. Abstract: Objectives: In 2010, a new subtype of salivary gland cancer (SGC), (mammary analogue) secretory carcinoma (SC), was defined, characterized by the ETV6-NTRK3 fusion gene. As clinical behavior and outcome data of this histological subtype tumor are still sparse, we aimed to describe the clinicopathological course and outcome of a series of translocation positive SC patients. Patient and methods: We re-evaluated the pathological diagnosis of a subset of SGCs, diagnosed in 4 of 8 Dutch head and neck centers. Subsequently, tumors with a morphological resemblance to SC were tested for the ETV6-NTRK3 fusion gene using RT-PCR. Furthermore, patients prospectively diagnosed with SC were included. The clinical characteristics and outcomes were retrieved from the patient files. Results: Thirty-one patients with ETV6-NTRK3 fusion gene positive SC were included. The median age was 49 years, 17 patients (55%) were male. Eighteen tumors (58%) arose in the parotid gland. One patient presented with lymph node metastasis. All patients underwent tumor resection and 4 patients had a neck dissection. Four patients had re-resection and 15 patients (48%) received postoperative radiotherapy. One patient developed a local recurrence, no regional recurrences or distant metastases were observed. After a median follow-up of 49 months the 5- and 10-year overall survival were 95%, the 5- and 10-year disease free survival were 89%. Conclusion: The clinical course of SC is favorable with a low rate of locoregional recurrence and excellent survival. Given the low incidence of nodal metastases, elective neck treatment, i.e. surgery and/or radiotherapy, does not seem to be indicated.